A complete set of eigenstates for position-dependent massive particles in a Morse-like scenario - Correa, R. A.C. [UNESP]; de Souza Dutra, A. [UNESP]; de Oliveira, J. A. [UNESP]; Garcia, M. G. [UNESP] (AIP Publishing, 2017)
In this work, we analyze a system consisting in two-dimensional position-dependent massive particles in the presence of a Morse-like potential in two spatial dimensions. We obtain the exact wavefunctions and energies for a complete set of eigenstates for a given dependence of the mass with the spatial variables. Furthermore, we argue that this scenario can play an important role to construct more realistic ones by using their solution in perturbative approaches.